Fluorescent whitening agents in Baiyangdian Lake in North China: Analysis, occurrence, distribution and ecological risk assessment. (15th December 2021) - Wu, Qi; He, Bowen; Guo, Ruiyao; Cui, Jiansheng; Yan, Shuwen; Liu, Daxi; Yao, Bo
Abstract: Fluorescent whitening agents (FWAs) are very important chemical additives that are widely applied in the industrial production field. The history of global FWA production and use spans more than 60 years, but the environmental fate of FWAs has been less reported in the public literature and most studies predate 2000; in addition, the studied FWAs were still limited to FWA71 and FWA351. In this study, the occurrence and distribution of 9 commonly used FWAs in a lake in North China were reported for the first time. We found that 6 target FWAs were prevalent in the lake, and the concentration levels were usually at the ng L −1 level. Decreasing FWA levels with increasing distance from the estuary area were observed in summer. FWA135, FWA185, and FWA367, the most detected 3 FWAs, with the ecological risk at high levels, and ΣRQ >10 were obtained from all the investigated samples, suggesting that all the sampling sites could be considered with certain ecological risk for aquatic life. As a category of heavily and widely used dyes, FWAs in environmental media have been ignored for a long time. Substantial additional research needs to be conducted to determine the environmental behavior and ecological toxicology of FWAs. Graphical abstract: Image 1 Highlights: Nine Fluorescent Whitening Agents (FWAs) in China were reported for the first time. Most target FWAs were ubiquitous in water samples but at trace levels (<10 μg L −1 ). Decreasing FWA levels with increasing distance from the estuary area were observed. All the sampling sites were considered with certain ecological risk for aquatic life.